Diagnostic performance of 18F-FDG PET/CT in solitary pulmonary nodules of non-smokers - Karyagar, Sevda Saglampinar; Koc, Zehra Pinar; Karyagar, Savas; Bekar, Yildiray (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2017)
Background: This study aims to investigate the diagnostic performance of fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (F-18-FDG PET/CT) in patients with solitary pulmonary nodules without smoking history. Methods: A total of 38 patients (25 females, 13 males; mean age 63 +/- 14 years; range 23 to 84 years) with solitary pulmonary nodules without smoking history who underwent 18F-FDG PET/CT imaging between June 2009 and March 2013 were retrospectively analyzed. Medical history was obtained from each patient, and malignancy was initially made by computed tomography in all patients. The diagnosis was further confirmed by either histopathological analysis results or at least two-year follow-up results. Results: The mean lesion diameter was 20 +/- 6 (range 8 to 28) mm. Eleven patients had a lung carcinoma, predominantly an adenocarcinoma (n=10), while 10 patients were found to have a FDG-avid tumor. The sensitivity, specificity, accuracy, and positive predictive and negative predictive values of F-18-FDG PET/CT were 91%, 63%, 71%, 50%, and 94%, respectively. All patients diagnosed with malignancy were women with an advanced age. Only one of the male patients had a malignant nodule. Conclusion: The sensitivity and negative predictive value of F-18-FDG PET/CT were found to be high in non-smoker patients with solitary pulmonary nodules, although adenocarcinomas were predominant in our study.
Keywords: Computed tomography; fluorodeoxyglucose; non-smokers; positron emission tomography; solitary pulmonary nodule